2012
DOI: 10.6060/mhc2012.120577i
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Thiadiazole Hemihexaporphyrazine Bearing iso-Propyloxy Groups and its Trinuclear NiII Complex

Abstract: A thiadiazole derived expanded "hemihexaporphyrazine" of ABABAB-type has been prepared via cyclomerization reaction of 2,5-diamino-1,3,4-thiadiazole and 3,6-diisopropyl

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…[9,10] With the goal of detailed characterization and revealing potential applications of this young class of compounds, substituted and unsubstituted thiadiazoloporphyrinoids have been obtained very recently. [3,7,11,12] It has been found that unsubstituted thiadiazoloporphyrinoids are insoluble in most of organic solvents. An introduction of bulky substituents on the periphery of their molecules led to a significant increase of their solubility that allowed a purification and characterization.…”
Section: +mentioning
confidence: 99%
“…[9,10] With the goal of detailed characterization and revealing potential applications of this young class of compounds, substituted and unsubstituted thiadiazoloporphyrinoids have been obtained very recently. [3,7,11,12] It has been found that unsubstituted thiadiazoloporphyrinoids are insoluble in most of organic solvents. An introduction of bulky substituents on the periphery of their molecules led to a significant increase of their solubility that allowed a purification and characterization.…”
Section: +mentioning
confidence: 99%
“…[7][8][9] Among expanded compounds, Mc's of ABABAB-type (hemihexaphyrazine, H 3 Hhp) containing six consecutively interlinked 1,3,4-thiadiazole (A) and isoindole (B) subunits bridged by nitrogen atoms [10,11] induce a particular interest. Indeed, various substituted macroheterocyclic compounds of this type were synthesized to date [12][13][14][15][16][17][18] and their structures were confirmed by gas electron diffraction (GED) [19,20] and single crystal X-ray diffraction [21] methods. It was established that compounds of this type have a nonaromatic macrocyclic backbone containing 30 carbon and nitrogen atoms which form an expanded coordination cavity compared to that of porphyrins and phthalocyanines.…”
Section: Introductionmentioning
confidence: 99%